Kepemimpinan Kepala Madrasah Ibtidaiyah dalam Implementasi Permendikbud Nomor 23 Tahun 2015 - Siswadi Siswadi; Fauzan Mukti Mangkutaruno; Nanda Tri Lestari; Vina Aenu Fitri; Umi Hasanah (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2021)
This study aims to describe the leadership practices of the head of MI Ma'arif NU Kedungwringin Banyumas in the implementation of Permendikbud Number 23 of 2015. The study was conducted using qualitative approach with a phenomenological research. Data were collected through interview, observation and documentation and then analyzed using Miles and Huberman model. The results showed that there are five efforts done by the head of MI Ma'arif NU Kedungwringin Banyumas in leading his institution to implement Permendikbud No. 23 of 2015. First, initiating a habituation activities program for students with teachers and madrasa committees. Second, preparing and managing the budget for the implementation of the habituation programs for the students with the teachers and madrasa committee. Third, assisting madrasa residents in the implementation of habituation activity programs for students. Fourth, apply healthy rules to support the implementation of habituation activities for students. Fifth, make efforts to improve the habituation activity program for students.